Association between serum albumin and pulmonary function in adolescents: analyses of NHANES 2007–2012 - Qiao Liu; Biao Wu; Ruijie Xie; Yuling Luo; Du Zheng; Guang Liu; Huihai Zhang (BMC Pulmonary Medicine, 2024)
Abstract Background Pulmonary function tests (PFTs) are an important tool for assessing pulmonary diseases, although clinicians often find it challenging to accurately evaluate the pulmonary function of children. Methods We intend to investigate the association between serum albumin (SA) and lung function among U.S. adolescents. This cross-sectional study included 3,072 adolescents (aged 12 to 19) from 2007 to 2012National Health and Nutrition Examination Survey (NHANES). PFTs, including forced vital capacity (FVC)%predicted, forced expiratory volume in 1 s (FEV1)%predicted, FEV1/FVC%predicted, and maximum mid-expiratory flow (FEF25-75) % predicted, were utilized to assess the association between serum albumin levels and lung function. To explore the potential associations between SA and pulmonary function, we employed multivariate linear regression, subgroup analysis, smoothing curve fitting and threshold effect. Results A positive correlation was observed between serum albumin levels and pulmonary function. In the model with a fully adjusted, each 1 g/dL serum albumin increase in SA corresponded to an increase of 2.69% in FVC%pred, 5.8% in FEV1%pred, 10.99% in FEF25–75%pred and 2.98% in FEV1/FVC%pred. This association between SA and FEV1%pred differed across gender subgroups. A non-linear relationship was observed between SA and FEV1/FVC%pred. Conclusion Our results demonstrated a positive correlation between SA and lung function, suggesting a novel modality for evaluating pulmonary function, specifically in children. Clinical trial number Not applicable.